PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI MELALUI MEDIA PEMBELAJARAN EDUCAPLAY - Ulfa Salsabila; Yumna; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the mathematics learning outcomes of sixth-grade students through the use of Educaplay learning media. The research was motivated by the low learning outcomes of students, as indicated by many students who had not achieved the minimum mastery criteria. The research method used was Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 11 sixth-grade students. Data collection techniques were carried out through learning outcome tests and observations. The results showed that the use of Educaplay learning media was able to improve students' learning outcomes. In the pre-cycle stage, the average score of students was 41.82 with a mastery level of 27.27%. In cycle I, the average score increased to 74.55 with a mastery level of 54.55%. In cycle II, the average score reached 85.82 with a mastery level of 81.82%. These results indicate that Educaplay learning media is effective in improving mathematics learning outcomes of elementary school students.